IMPLEMENTATION OF CHARACTER EDUCATION FOR PARTICIPANTS IN CLASS IV SDN 5 SINDANGKASIH - MUSTOIP, SOFYAN (International Journal Pedagogy of Social Studies, 2018)
Students at this time, lack of polite attitude especially to teachers who should be respected. The sense of courtesy can be seen when the students shake hands with the teacher they meet, say "excuse" when passing the more mature person, especially the teacher they often meet in the school, and the number of learners who use slang compared to using Sundanese. Thus, this study has a purpose to describe intactly about the efforts made State Primary School 5 Sindangkasih in carrying out character education activities for students in class IV in order to shape the character of learners through local wisdom Sundanese culture. The method used in this research is descriptive qualitative method using interactive model in data analysis activities include data collection activities, data reduction, data presentation, to conclusion. The data collection is done through triangulation of data that is interview, observation, and documentation.